Analisis Potensi Energi Listrik Tenaga Surya Atap Pada Gedung PT.WNS Menggunakan Software Helioscope - Dymas Halim; Ahmad Dani; Beni Satria (CV. Hawari, 2026)
The use of rooftop solar power plants is one of the strategic solutions to support the energy transition and increase use of renewable energy in the industrial sector. This study aims to analyze the potential and performance of rooftop solar power plants at PT. Waruna Nusa Sentana building located in Medan City, North Sumatra, using a simulation approach based on HelioScope software. The analysis was carried out by utilizing Typical Meteorological Year weather data and technical parameters of the Photovoltaic (PV) system designed according geographical conditions and tropical climate of the study location. simulation results show that rooftop solar power system with an installed capacity of 47.36 kWp is capable of producing 66,699 kWh of annual electrical energy with a specific yield of 1,408.3 kWh/kWp/year. The system performance evaluation resulted in a performance ratio of 80.2%, indicating that the rooftop solar power system works efficiently and is in the good performance category for tropical regions. Loss analysis indicates that the largest energy losses come from the effects of cell temperature, followed by losses due to module mismatch, reflection, and losses in the inverter and AC system. Manual calculations performed as analytical verification demonstrated consistency with the simulation results, thus strengthening the validity of the approach used. This study demonstrates that the implementation of rooftop solar power plants in industrial buildings in Medan City is technically feasible and can be used as a reference in the planning and development of rooftop solar power plants in tropical regions with similar climate characteristics